Matrilateral Bias in Human Grandmothering - Daly, Martin; Perry, Gretchen (Frontiers in Sociology, 2017)
Children receive more care and resources from their maternal grandmothers than from their paternal grandmothers. This asymmetry is the "matrilateral bias" in grandmaternal investment. Here we synopsize the evolutionary theories that predict such a bias, and review evidence of its cross-cultural generality and magnitude. Evolutionists have long maintained that investing in a daughter's child yields greater fitness returns, on average, than investing in a son's child because of paternity uncertainty: the son's putative progeny may have been sired by someone else. Recent theoretical work has identified an additional natural selective basis for the matrilateral bias that may be no less important: supporting grandchildren lightens the load on their mother, increasing her capacity to pursue her fitness in other ways, and if she invests those gains either in her natal relatives or in children of a former or future partner, fitness returns accrue to the maternal, but not the paternal, grandmother. In modern democracies, where kinship is reckoned bilaterally and no postmarital residence norms restrict grandmaternal access to grandchildren, many studies have found large matrilateral biases in contact, childcare, and emotional closeness. In other societies, patrilineal ideology and postmarital residence with the husband's kin (virilocality) might be expected to have produced a patrilateral bias instead, but the available evidence refutes this hypothesis. In hunter-gatherers, regardless of professed norms concerning kinship and residence, mothers get needed help at and after childbirth from their mothers, not their mothers-in-law. In traditional agricultural and pastoral societies, patrilineal and virilocal norms are common, but young mothers still turn to their natal families for crucial help, and several studies have documented benefits, including reduced child mortality, associated with access to maternal, but not paternal, grandmothers. Even in rural China and Bangladesh, where women's links to their natal families are formally severed at marriage, critical matrilateral assistance persists "under the radar". Our review is limited to grandmothers, but the relevant evolutionary theories are not, and there is empirical evidence that the matrilateral bias extends to other kin, too. We propose that it is an evolved aspect of human nature.